Improving implementation of school-based healthy eating and physical activity policies, practices, and programs: a systematic review. Issue 7 (3rd June 2021) - Barnes, Courtney; McCrabb, Sam; Stacey, Fiona; Nathan, Nicole; Yoong, Sze Lin; Grady, Alice; Sutherland, Rachel; Hodder, Rebecca; Innes-Hughes, Christine; Davies, Marc; Wolfenden, Luke
Abstract: Although best practice recommendations exist regarding school-based healthy eating and physical activity policies, practices, and programs, research indicates that implementation is poor. As the field of implementation science is rapidly evolving, an update of the recent review of strategies to improve the implementation of healthy eating and physical activity interventions in schools published in the Cochrane Library in 2017 was required. The primary aim of this review was to examine the effectiveness of strategies that aim to improve the implementation of school‐based policies, practices, or programs to address child diet, physical activity, or obesity. A systematic review of articles published between August 31, 2016 and April 10, 2019 utilizing Cochrane methodology was conducted. In addition to the 22 studies included in the original review, eight further studies were identified as eligible. The 30 studies sought to improve the implementation of healthy eating ( n = 16), physical activity ( n = 11), or both healthy eating and physical activity ( n = 3). The narrative synthesis indicated that effect sizes of strategies to improve implementation were highly variable across studies. For example, among 10 studies reporting the proportion of schools implementing a targeted policy, practice, or program versus a minimal or usual practice control, the median unadjusted effect size was 16.2%, ranging from –0.2% to 66.6%. Findings provide some evidence to support the effectiveness of strategies in enhancing the nutritional quality of foods served at schools, the implementation of canteen policies, and the time scheduled for physical education.